The pain is not from the uterus: a rare complication of ovarian cyst during term labour - M. Adzlan, Fadzlin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
A case of primigravida with an ovarian torsion at 39 weeks of gestation is reported here. A Malay lady in her late 20s with a known case of ovarian cyst complained of sudden onset of severe pain during labour. Diagnosis of ovarian torsion was made and she underwent laparotomy cystectomy with emergency lower segment caesarean section in the same setting. Post-operative recovery was unremarkable. Histopathological examination confirmed mucinous cystadenoma.